2013
DOI: 10.1021/ie400918x
|View full text |Cite
|
Sign up to set email alerts
|

Rigorous Design of Complex Distillation Columns Using Process Simulators and the Particle Swarm Optimization Algorithm

Abstract: We present a derivative-free optimization algorithm coupled with a chemical process simulator for the optimal design of individual and complex distillation processes using a rigorous tray-by-tray model. The optimal synthesis of complex distillation columns is a non-trivial problem due to the discrete nature of the tray-by-tray column model, and also because of the high degree of non-linearity and non-convexity of the underlying MESH equations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 46 publications
0
49
0
Order By: Relevance
“…The optimization methods have been applied to design several chemical processess (other than crude oil distillation units) [20][21][22][23][24] .…”
mentioning
confidence: 99%
“…The optimization methods have been applied to design several chemical processess (other than crude oil distillation units) [20][21][22][23][24] .…”
mentioning
confidence: 99%
“…This is due to the presence of discrete variables such as feed location, and number of trays in different column sections, as well as the nonconvexity of the MESH equations. Javaloyes-Antón et al [25], reviewed the application of MINLP formulations for the solutions of complex distillation columns (including DWCs), and concluded that based on the high nonlinearities of these formulations, as well as sophisticated initialization techniques needed to obtain feasible solutions (only local optima are guaranteed as the solutions are highly dependent on the initialization points), these methods are complex and suited only for those skilled enough to adapt them for their own requirements.…”
Section: Introductionmentioning
confidence: 99%
“…However, they are not able to guarantee that the solutions found are optimal. Though derivative-based search methods can theoretically offer local optimality guarantees, they are not easily amenable to highly complex real world problems and might be unable to find solutions which are as good as those obtained by derivative-free algorithms [25,26]. Examples of these derivative-free algorithms include genetic algorithms (GA), simulated annealing, particle swarm optimization (PSO) among others.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations